Smart university implementation in higher education to improve the graduates’ competitiveness - Amron Amron; Febrianur Ibnu Fitroh Sukono Putra; Risanda Alirastra Budiantoro; Masitha Fahmi Wardhani (Universitas Negeri Yogyakarta, 2022)
This research aimed to implement a smart university to optimize the three higher education principles aka Tri Dharma Perguruan Tinggi (Education Dharma, Research Dharma, and Community Service Dharma). A strategic step that can be taken is to apply digitalization to increase the selling value of universities in the education industry and increase the usefulness of the satisfaction of lecturers and students. The research is exploratory qualitative using interviews, observations, and literature studies as data collection techniques. The sampling method used was non-probability sampling (purposive sampling). The findings show that several supporting factors that influence the optimization of the three principles of higher education are the flexibility of the workplace and time, as well as the use of information technology which is easier to use and has high accessibility. Facilities and infrastructure are supporting elements. The hardware and software infrastructure condition in universities is still inadequate to support a quality learning process. Universities need to improve the performance of educators and education staff.